The First Regularized Trace of the Sturm-Liouville Operator With Robin Boundary Conditions - Pavlović Komazec , Nataša; Vojvodić, Biljana (Sarajevo Journal of Mathematics, 2024)
This paper deals with the boundary value problem for the operator Sturm-Liouville type D^2=D^2(h, H, q_1,q_2,τ,φ) generated by -y''(x)+_i=1^2q_i(x)y(x-iτ)=λ y(x), x[0, π] y'(0)-hy(0)=0, y'(π)+Hy(π)=0 where π3≤ τ <π2 , h, HR{0} and λ is a spectral parameter. We assume that q_i, i=1,2 are real-valued potential functions from L_2 [0, π]. We establish a formula for the first regularized trace of this operator. 2020 Mathematics Subject Classification. 34B09, 34B24, 34L10